Higher minimum wage, better labour market returns for rural migrants? Evidence from China - Yanjun Ren; Yanling Peng; Bente Castro Campos; Houjian Li (Economic Research-Ekonomska Istraživanja, 2021)
Using data from the 2013 China Household Income Project (CHIP), this study investigates the effects of minimum wages on labour market returns for rural migrants in China and sheds light on the potential underlying mechanisms of these effects. An instrumental variable estimation is used to address the endogeneity problem of minimum wages on labour market returns. Our empirical findings indicate that minimum wages have positive effects on migrants' wages. Specifically, we observe higher effects for women and migrants who have higher education levels. Regarding the possible mechanisms through which minimum wages influence migrants' labour market returns, we find that minimum wages tend to increase rural migrants' working time but have no significant effects on allowances related to work. We could not obtain conclusive results for social insurance due to its potential endogeneity.
Keywords: J38; J31; J33; 330; minimum wage; rural migrants; labour market returns; China